Temporal expectations in delay of gratification. Issue 1 (7th December 2022) - Haynes, Jeremy M.; Willis‐Moore, Mariah E.; Perez, D.; Cousins, Devanio J.; Odum, Amy L.
Abstract : We examined how temporal expectations influence preference reversals in a delay of gratification task for rats based on a hypothesis of Rachlin (2000), who suggested that preference for a larger‐later reward may shift in favor of a smaller‐immediate reward as a result of changes in when that larger reward is expected. To explore Rachlin's hypothesis, we preexposed two groups of rats to the delays associated with a larger‐later reinforcer from a delay of gratification task. One group experienced the delays as a function of their choices in an intertemporal choice task and the other group experienced delays yoked from the first group (independent of their behavior) in an exposure training procedure. In addition, we included a third group of rats that were not exposed to delays during preexposure training as a comparison to the other two groups. Overall, the two groups of rats that experienced delays during preexposure training tended to make fewer defection responses than the comparison group during the delay of gratification task. Consistent with Rachlin's hypothesis, our results suggest that temporal learning may influence preference reversals in a delay of gratification task, providing a number of future directions for research in this area.